Spontaneous delivery or manual delivery of the placenta during caesarean: A randomized controlled trial - Pokharel, SM (Journal of College of Medical Sciences-Nepal, 2012)
The study was done to compare the blood loss and the time between spontaneous delivery and manual removal of the placenta during caesarean section. We prospectively randomized and compared outcomes of 100 gravid women with manual (n=50) and spontaneous (n=50) placental delivery at caesarean section. Blood loss was measured after placental deliverey at caesarean and was greater in the manually delivered group (100.9 ± 22.5 ml) than in the spontaneous delivery group. (55.11 ±21.07 ml) P< 0.001. The mean interval during the delivery of the newborn and the placenta is longer in spontaneous delivery group (62.02 vs. 50.5 seconds), but the mean duration of the operation was similar. Spontaneous delivery of the placenta as compared to manual expression significantly reduces the blood loss without increasing the operating time. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 23-28 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6676